Optics and Photonics for Counterterrorism and Crime Fighting VI and Optical Materials in Defence Systems Technology VII 2010
DOI: 10.1117/12.868950
|View full text |Cite
|
Sign up to set email alerts
|

Fibre loop cavity ring-down spectroscopy for the sensitive and selective detection of minute sample volumes of liquid explosives

Abstract: Fibre loop cavity ring-down spectroscopy (FLCRDS) is a relatively new technique, which extends the more commonly used two-mirror cavity ring-down spectroscopy (CRDS) technique to measurements of optical absorption by minute liquid sample volumes. In this paper, loops of 50 μm-core-diameter multimode optical fibre were used to carry out both direct and evanescent wave FLCRDS measurements at 532 nm. The sensitivity of each technique was established by making measurements on a common dye, rhodamine 6G; detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Most of the previous cavity-based measurements have been made on gas-phase analytes as low background scattering and absorption by gases allows a very high number of passes (>10 4 with suitable high reflectivity mirrors) to be achieved. Only a few liquid-phase, cavity-based studies have been reported to date as the solvent-related scattering and absorption losses are much higher. However, for bioanalytical applications the majority of analytes are in the liquid-phase. Many of the previous liquid-phase studies have used CRDS and have focused on using CRDS as a detection method for high performance liquid chromatography (HPLC).…”
mentioning
confidence: 99%
“…Most of the previous cavity-based measurements have been made on gas-phase analytes as low background scattering and absorption by gases allows a very high number of passes (>10 4 with suitable high reflectivity mirrors) to be achieved. Only a few liquid-phase, cavity-based studies have been reported to date as the solvent-related scattering and absorption losses are much higher. However, for bioanalytical applications the majority of analytes are in the liquid-phase. Many of the previous liquid-phase studies have used CRDS and have focused on using CRDS as a detection method for high performance liquid chromatography (HPLC).…”
mentioning
confidence: 99%